Effectiveness of Licensing Services Through the Sicantik Cloud Application in the Department of Capital Investment and One-Door Integrated Services in Batu Bara District - Ahmad Bukhari; Humaizi; Nurman Achmad (Formosa Journal of Social Sciences (FJSS), 2024)
This study aims to examine The Effectiveness of Licensing Services via the SiCANTIK Cloud Application at the Batu Bara Regency Investment and One-Stop Integrated Services Service. This type of te research is descriptive with a qualitative approach. The research location is at the Batu Bara Regency Investment and One-Stop Integrated Services. informant selection techniques purposive sampling. This research uses data collection techniques: observation, interviews and documentation. The results of this research are that Licensing Services via the SiCANTIK Cloud Application at the Batu Bara Regency Investment and One-Stop Integrated Services Service are still not effective when viewed based on several indicators in the theory of effectiveness according to Duncan in steers, including (1) goal achievement; (2) integration; and (3) Adaptation of the SiCANTIK Cloud Application in providing licensing services in Batu Bara Regency